Rinsing solutions containing natural extracts and fluoride prevent enamel erosion in vitro - Tommy BAUMANN; Samira Helena NIEMEYER; Adrian LUSSI; Taís SCARAMUCCI; Thiago Saads CARVALHO (University of São Paulo, 2023)
Abstract Polyphenols interact with salivary proteins and thus can improve the pellicle's erosion protective properties. This effect could be exploited to create rinsing solutions with polyphenols as active ingredients for erosion prevention. Different from the current gold standard for erosion protective rinsing solutions, these rinses would not rely on stannous ions. This would offer alternatives for patients with concerns regarding the composition of rinsing solutions and preferring bio-products. Objective To develop an erosion-preventive rinsing solution containing natural polyphenol-rich extracts. Methodology Solutions were prepared with polyphenols from either grapeseed extract or cranberry extract, 500 ppm fluoride added, and additionally flavors and sweeteners. Controls were deionized water, 500 ppm fluoride solution, and the gold standard rinse in the field (Sn2+/F-). In total, 135 enamel specimens (n=15/group) were subjected to five cycles of salivary pellicle formation (30 min, 37°C), modification with the solutions (2 min, 25°C), further salivary pellicle formation (60 min, 37°C), and erosive challenge (1 min, 1% citric acid, pH 3.6). Relative surface microhardness (rSMH), surface reflection intensity (rSRI), and amount of calcium release (CaR) were investigated. Data were analyzed with Kruskal-Wallis and Wilcoxon rank sum tests (α=0.05). Results The polyphenol solutions containing fluoride, as well as additional flavors, protected enamel better than fluoride alone, and similar to the Sn2+/F- solution, when investigating both rSMH and CaR. When measuring rSRI, Sn2+/F- showed the best protection, while the polyphenol solutions were similar to fluoride. Conclusion For two of the three assessed parameters (rSMH and CaR), both developed polyphenol-rich rinsing solutions were able to protect enamel from erosion, improving/potentializing the effect of fluoride and matching the protection offered by the current gold standard rinsing solution.